Observations on the biology of Afrotropical Hesperiidae (Lepidoptera). Part 7. Hesperiinae incertae sedis: grass and bamboo feeders - Cock, Matthew J. W.; Congdon, T. Colin E. (Zootaxa, 2014)
Partial life histories for 17 Hesperiinae incertae sedis that feed on grasses or bamboos (Poaceae) are described and illustrated. The genera dealt with are: Astictopterus (from Evans’ (1937) Astictopterus group), Prosopalpus, Kedestes (from Evans’ (1937) Ampittia group), Ceratrichia, Pardaleodes, Ankola (From Evans’ (1937) Ceratrichia and Acleros groups), Perrotia (part), Chondrolepis, and Monza (part) (all from Evans’ Ploetzia genera group). The Poaceae-feeders comprise a relatively small proportion of the Afrotropical Hesperiinae fauna, particularly the mainland Afrotropical fauna. The caterpillars shown here are fairly homogeneous, with the head wider nearer the base, and lacking obvious setae on the body. Wax glands have been noted over most of the ventral surface A1–A8 in the final instar of Ceratrichia, Pardaleodes and Monza, but are absent in Chondrolepis, and either absent or not documented for other genera. The short double frontal projection of Tsitana uitenhaga is unusual, but pupae of the congeneric species have not been documented. The pupae of Kedestes spp. generally have extensive black or dark areas. The pupae of Pardaleodes and Ankola are very flimsy and collapse after emergence. All known pupae of Chondrolepis spp. have a short, blunt downturned frontal projection, not seen for any other Afrotropical genera, although Semalea spp. may have a short blunt projection. The remaining pupae are all generally similar and undistinguished. These are not substantial differences, but suggest that pupal characters may be useful in grouping some of the genera of Afrotropical Hesperiinae incertae sedis.